Human Calmodulin Mutations - Jensen, Helene H.; Brohus, Malene; Nyegaard, Mette; Overgaard, Michael T. (Frontiers in Molecular Neuroscience, 2018)
Fluxes of calcium (Ca2+) across cell membranes enable fast cellular responses. Calmodulin (CaM) senses local changes in Ca2+ concentration and relays the information to numerous interaction partners. The critical role of accurate Ca2+ signaling on cellular function is underscored by the fact that there are three independent CaM genes (CALM1-3) in the human genome. All three genes are functional and encode the exact same CaM protein. Moreover, CaM has a completely conserved amino acid sequence across all vertebrates. Given this degree of conservation, it was long thought that mutations in CaM were incompatible with life. It was therefore a big surprise when the first CaM mutations in humans were identified six years ago. Today, more than a dozen human CaM missense mutations have been described, all found in patients with severe cardiac arrhythmias. Biochemical studies have demonstrated differential effects on Ca2+ binding affinities for these CaM variants. Moreover, CaM regulation of central cardiac ion channels is impaired, including the voltage-gated Ca2+ channel, CaV1.2, and the sarcoplasmic reticulum Ca2+ release channel, ryanodine receptor isoform 2, RyR2. Currently, no non-cardiac phenotypes have been described for CaM variant carriers. However, sequencing of large human cohorts reveals a cumulative frequency of additional rare CaM mutations that raise the possibility of CaM variants not exclusively causing severe cardiac arrhythmias. Here, we provide an overview of the identified CaM variants and their known consequences for target regulation and cardiac disease phenotype. We discuss experimental data, patient genotypes and phenotypes as well as which questions remain open to understand this complexity.